A SYNOPSIS OF THE EARLY DEVELOPMENTAL STAGES OF FISHES OF THE GENUS SARDINELLA VALENCIENNES FROM INDIAN WATERS WITH KEYS FOR THEIR IDENTIFICATION - Bensam, P (Indian Journal of Fisheries, 2011)
In the present synopsis, a brief resume of relevant literature published on the early stages of Sardinellaspecies is given, along with keys prepared for identification of the eggs, larvae and posflarvae, to theextent available. Some of the subtle characters to distinguish the eggs, larvae and postlarave of the speciesdescribed are brought out for their easy separation in plankton studies.